2018
DOI: 10.1002/anie.201710336
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Optical Imaging of the Growth of Conjugated Polymer Aggregates

Abstract: Understanding the mechanisms that contribute to conjugated polymer aggregate formation and growth may yield enhanced control of aggregate morphology and functional properties on the mesoscopic scale. In situ optical imaging of the growth of MEH-PPV aggregates in real time in controlled swollen films shows that growth occurs through multiple mechanisms and is more complex than previously described. Direct evidence is provided for both Ostwald ripening and aggregate coalescence as operative modes of aggregate gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…We speculate that the prevalence of the good solvent may influence the character of the aggregation. In this case, additional aggregation processes such as coalescence may also play a role besides the usual Ostwald ripening during aggregation …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We speculate that the prevalence of the good solvent may influence the character of the aggregation. In this case, additional aggregation processes such as coalescence may also play a role besides the usual Ostwald ripening during aggregation …”
Section: Figurementioning
confidence: 99%
“…Such a low energy transfer efficiency could arise, if coalescence occurs during aggregation. If two aggregates showing γ‐phase and β‐phase coalesce, the coupling to the energetically lower‐lying β‐phase could be sufficiently weak so that emission from both phases becomes visible.…”
Section: Figurementioning
confidence: 99%
“…124 More recently, Yang et al followed the growth of MEH-PPV aggregates in situ by tracking the aggregates as they diffused through PMMA films that were again swollen by exposure to acetone−chloroform vapor. 125 Their studies confirmed the importance of Ostwald ripening in aggregate growth but also revealed that some aggregates grew by coalescence of smaller aggregates. Figure 8 shows particle tracking results that depict aggregate growth by coalescence.…”
Section: ■ Conjugated Polymersmentioning
confidence: 83%
“…Early investigations pointed to the importance of Ostwald ripening in the aggregation of MEH-PPV dispersed in PMMA . More recently, Yang et al followed the growth of MEH-PPV aggregates in situ by tracking the aggregates as they diffused through PMMA films that were again swollen by exposure to acetone–chloroform vapor . Their studies confirmed the importance of Ostwald ripening in aggregate growth but also revealed that some aggregates grew by coalescence of smaller aggregates.…”
Section: Conjugated Polymersmentioning
confidence: 99%
“…49 The swelling invoked by the solvent vapor introduced to the system allows for conjugated polymer chain diffusion and aggregation via Ostwald ripening and/or particle coalescence. 46 Here, we use a multimodal apparatus previously described that affords control over the aggregation process and simultaneous wide-field fluorescence imaging 54 to characterize aggregates of MEH-PPV in PMMA. In contrast to our previous work focused on MEH-PPV initially dissolved in toluene, 45 which supports a collapsed and ordered conformation, here we study MEH-PPV initially dissolved in chloroform, which supports the random coil conformation at the single-molecule level.…”
Section: ■ Introductionmentioning
confidence: 99%